Impact of Cooling Rate on the Rheological Properties of Flooded Crude Oils - Ismayilova, F.B.; Zeynalova, G.A. (Herald of Azerbaijan Engineering Academy, 2024)
The article presents the results of studies on the influence of the water ratio factor and the cooling rate on the rheological properties of anomalous crude oils. Laboratory studies have shown that an increase in the water content in emulsions of more than 40% leads to a significant increase in viscosity over the entire temperature range. It is also shown that an increase in water ratio increases the pour point of oil by 7÷14 0C.